Novel usage of superficial liposuction in hidradenitis suppurativa - Ahmad Zaidi, Ahmad İbrahim; Mat Saad, Arman Zaharil (Journal of Surgery and Medicine, 2019)
Hidradenitis suppurativa otherwise known as acne inversa is a common skin disease that presents as recurrent painful nodules, which form in characteristic sites of the body and often progress to chronic purulent discharge, scarring, and sinus formation. Currently there is no gold standard treatment to combat this recurring disease. Here we describe a novel usage of superficial liposuction in treatment of hidradenitis suppurativa.